1998
DOI: 10.1152/ajplung.1998.275.2.l269
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms and role of endothelin-1-induced calcium oscillations in pulmonary arterial myocytes

Abstract: The effect of endothelin (ET)-1 on both cytosolic Ca2+ concentration ([Ca2+]i) and membrane current in freshly isolated myocytes, as well as on the contraction of arterial rings, was investigated in rat main pulmonary artery (RMPA) and intrapulmonary arteries (RIPA). ET-1 (5–100 nM, 30 s) induced a first [Ca2+]ipeak followed by 3–5 oscillations of decreasing amplitude. In RMPA, the ET-1-induced [Ca2+]iresponse was fully abolished by BQ-123 (0.1 μM). In RIPA, the response was inhibited by BQ-123 in only 21% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 38 publications
9
53
1
Order By: Relevance
“…A similar effect has been observed with NPPB on vasopressin-induced [Ca 2 þ ] i transients in A7r5 cells (Pon et al, 1993). However, in contrast to these studies, NFA (50 mM) has been shown to have no effect on the endothelin-1-induced Ca 2 þ oscillations in freshly isolated rat PASMCs (Hyvelin et al, 1998), or on the 5-HT-induced [Ca 2 þ ] i transients in cultured rat PASMCs (Yuan, 1997).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A similar effect has been observed with NPPB on vasopressin-induced [Ca 2 þ ] i transients in A7r5 cells (Pon et al, 1993). However, in contrast to these studies, NFA (50 mM) has been shown to have no effect on the endothelin-1-induced Ca 2 þ oscillations in freshly isolated rat PASMCs (Hyvelin et al, 1998), or on the 5-HT-induced [Ca 2 þ ] i transients in cultured rat PASMCs (Yuan, 1997).…”
Section: Discussionsupporting
confidence: 66%
“…Despite a large number of studies examining the effect of Cl À channel blockers on the contractile and electrophysiological properties of smooth muscle, there have been very few studies that systematically look at the effect of these drugs on intracellular Ca 2 þ signalling (Pon et al, 1993;Yuan, 1997;Hyvelin et al, 1998). Thus, the objective of the present study was to determine the effect of four different Cl À channel blockers on caffeine-induced Ca 2 þ signalling in rat pulmonary artery smooth muscle cells (PASMCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In myocytes of rat main pulmonary artery, oscillation in intracellular Ca 2+ is presumed to be linked to vasomotion, with extracellular Ca 2+ making a very limited contribution (Hyvelin et al, 1998). As shown in the present investigation, vasomotion in the same blood vessel displays a higher order slow periodicity which does not appear to have been reported previously.…”
Section: Introductionsupporting
confidence: 54%
“…Accordingly, a functional SR would appear necessary for generating this pattern. Cycling and release of intracellular Ca 2+ are deemed to be necessary for vasomotion (Hyvelin et al, 1998;Haddock et al, 2002). Lee and colleagues (2001) waves.…”
Section: Role Of Srmentioning
confidence: 99%